2018
DOI: 10.1016/j.polymertesting.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Insights into crystallization and melting of high density polyethylene/graphene nanocomposites studied by fast scanning calorimetry

Abstract: Vourlias, G. (2018). Insights into crystallization and melting of high density polyethylene/graphene nanocomposites studied by fast scanning calorimetry. Polymer Testing, 67,[349][350][351][352][353][354][355][356][357][358] AbstractGraphene nanoplatelets (5 wt.%) with different diameters (5 and 25 x 10 -6 m in diameter, 6 x 10 -9 m in thickness) filled high density polyethylene nanocomposites were prepared by the melt-mixing method and the effect of graphene nanoplatelets on the polymeric matrix are then inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…This gave a significant reduction of melting temperature up to 3.8%. Moreover, Tarani et al [ 61 ] indicated that the addition of GNPs in HDPE decelerated the overall crystallization process of matrix. GNPs behave as a barrier during the mass transfer forming a tortuosity in the diffusion path, which decreases the free volume and retard the crystalline-amorphous interface movement [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…This gave a significant reduction of melting temperature up to 3.8%. Moreover, Tarani et al [ 61 ] indicated that the addition of GNPs in HDPE decelerated the overall crystallization process of matrix. GNPs behave as a barrier during the mass transfer forming a tortuosity in the diffusion path, which decreases the free volume and retard the crystalline-amorphous interface movement [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works on HDPE/GNP nanocomposites [ 33 , 34 , 35 ], it was found that GNP M25 with the larger diameter size reduced the chain mobility in the semi-crystal HDPE matrix causing the degradation of the HDPE to be retarded. The large contact areas and continuous paths increased the thermal conductivity values.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cazé and Chuah average Avrami models were also failed as neither took into account secondary crystallization process of the system . Using a fast scanning calorimetry method, Tarai and coworkers observed several melting events, associated with the small imperfect crystals grown at a large supercooling, for neat high‐density polyethylene (HDPE) and its nanocomposites containing graphene …”
Section: Introductionmentioning
confidence: 99%